Pengaruh Gaya Kepemimpinan Transformasional, Disiplin Kerja Dan Kompensasi Terhadap Kinerja Guru SMK Global Mulia Bekasi - Rismawati Rismawati; Ahmad Badawi Saluy (AMAR (Andalas Management Review), 2018)
The research aimed to determinie how much influence of Transformasional Leadership Style, Works Discipline and Compensation on teacher performance at SMK Global Mulia Bekasi partially and simultaneously. Sampling in this Research is done by using satuarated sampling technique. The sample used was 30 respondents from the population of 30 teachers. The data were collected by using questionnaires. The method used in this research is quantitative method. While The data analysis technique used is multiple linear regression analysis with the use of SPSS program version 24. The results showed that the three independent variables of transformational leadership style, work discipline and Compensation together partially or simultaneously have a positive and significant effect on Teacher Performance. Compensation is the biggest significant variabel in influencing the performance of SMK Global Mulia Bekasi Teachers.